Role of the mechanosensitive piezo1 channel in intervertebral disc degeneration. (8th December 2022) - Guo, Sheng; Wang, Chenglong; Xiao, Changming; Gu, Qinwen; Long, Longhai; Wang, Xiaoqiang; Xu, Houping; Li, Sen
Abstract: Intervertebral disc degeneration (IDD) is a multifactorial skeletal disease involving mechanical, genetic, systemic, and biological factors, and it is characterized by apoptosis of the nucleus pulposus cells and breakdown of the extracellular matrix (ECM), which will impair the structure and function of the intervertebral disc (IVD), and cause low back pain. Recently, the piezo1 is recognized as a critical mechanically activated ion channel of IDD. Numerous studies have reported that the piezo1 ion channel was aberrantly activated in the degenerated disc tissues and deeply participated in the pathogenesis of IDD. Inactivating or interfering with the piezo1 channel could effectively prevent the progression of IDD under the experimental conditions. It may be a promising target for the prevention and treatment of the disabling disease. Therefore, we have to make a comprehensive investigation and understanding of the mechanisms and functions of the piezo1 in the biomechanics of the spine. This study mainly elucidates the role of the piezo1 channel in IDD, which may facilitate the development of therapeutic targets for this disease.